2015
DOI: 10.2131/jts.40.21
|View full text |Cite
|
Sign up to set email alerts
|

JNK implication in adipocyte-like cell death induced by chemotherapeutic drug cisplatin

Abstract: -Recent evidence shows that tumor microenvironment containing heterogeneous cells may be involved in cancer initiation, growth and tumor cell response to anticancer therapy. Chemotherapy was designed to make toxic impact on malicious cells in organisms, however, the means to protect healthy cells against chemical toxicity are still unsuccessful. As known, the majority of tumor surrounding cells are cancer-associated adipocytes which influence cancer development, progression and treatment. Targeting the compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Various types of stimulation such as drugs and ultraviolet irradiation can induce c-Jun activation 43 . Activated c-Jun participates in various physiological processes such as proliferation and apoptosis of tumor cells by regulating target gene transcription 44 . A previous study showed that the interaction between KLF5 and c-Jun promoted Angiotensin II-induced suppression of p21 expression in vascular smooth muscle cells 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Various types of stimulation such as drugs and ultraviolet irradiation can induce c-Jun activation 43 . Activated c-Jun participates in various physiological processes such as proliferation and apoptosis of tumor cells by regulating target gene transcription 44 . A previous study showed that the interaction between KLF5 and c-Jun promoted Angiotensin II-induced suppression of p21 expression in vascular smooth muscle cells 45 .…”
Section: Discussionmentioning
confidence: 99%
“…We noted that cells were reduced after SP600125 treatment at later stages of trans-differentiation, and studies suggest that MAPKs participate in apoptosis [23, 24]. Data for all treatment groups show that (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Therefore, CBP is required for tumor growth through ERK1/2 phosphorylation and apoptosis regulation via inactivation of JNK in GIST882 cells, whereas p300 does not appear to contribute to these activities. However, both CBP and p300 silencing led to the upregulation of proapoptotic Bax and the downregulation of anti-apoptotic Bcl-2 and Bcl-xL, members of the Bcl-2 family that are involved in the mitochondrial cell death pathway (41), suggesting that CBP/p300 affect apoptosis through the regulation of Bcl-2 family proteins. Thus, CBP may regulate apoptosis via both the death receptor signaling pathway and the mitochondrial cell death pathway in GIST cells.…”
Section: Discussionmentioning
confidence: 99%